Pengembangan Buku Stimulasi dan Deteksi Tumbuh Kembang Anak Usia Dini Berbasis ICT - Rantina, Mahyumi; Hasmalena, Hasmalena; Karmila Nengsih, Yanti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
In the current era of globalization, parents, teachers, and all elements of society who are in the environment around early childhood learn to provide stimulation that is following the development of children. The wider and more open parenting science that can be accessed by parents, teachers and the community requires appropriate guidelines as a reference source to detect and stimulate children's development based on facts in the field. This is the background for researchers to develop and produce a book on stimulation and early detection of ICT-based early childhood development that is valid and practical. The research method used is Research and Development with the ADDIE model with requirements analysis procedures, prototype design, development, and evaluation implementation. The evaluation technique used is the Tessmer evaluation. Data collection techniques using observation, interviews, and documentation. The results of the research from experts, namely material experts and media design experts with very valid categories with proportions of 95.45% and 89.58% respectively, so that the product is feasible to be continued on a small-scale trial. So that the development of a guidebook for stimulation and early detection of growth for children aged 0-6 years is very valid to be tested as a guidebook for teachers and parents in stimulating and detecting the growth of children aged 0-6 years.